The Usage of Aloe Vera Extract as a Natural Disinfectant to reduce Total Coliform in River Water: The Usage of Aloe Vera Extract as a Natural Disinfectant to reduce Total Coliform in River Water - Kumalasari, Vita - (Universitas Muhammadiyah Kalimantan Timur, 2022)
The population growth has experienced enhancement year by year. It is in line with the increasing demand for clean water. Nevertheless, the pressure of human needs and handling of water causes the quality of water continues to decline. Based on the result of total Coliform bacteria test in Code River taken in Suryatmajan, Danurejan, Yogyakarta, it is shown that the bacteria result has exceeded the quality standard, 2400 x 103 MPN/100mL. Aloe vera leaves are potential to be used as natural disinfectant because of the active ingredients content anthraquinones (aloe-emodin, chrysophanol), anthranols (saponin, aloesapanol-I, II), anthrones (aloin A & B), pyrones (aloenin), chromones (aloesin), isoflavone glycoside, acemannan, carboxypeptidase, lectin (aloctin A & B), lignin. This research aims to determine the most optimum concentration of aloe vera extract to lower the Coliform numbers in Code River water. This research is an experimental research using One Group Pretest Posttest. Aloe vera was extracted by maceration method using 70% ethanol. The concentration of Aloe vera extract added into the river water sample was 20 mL/L, 30 mL/L, 40 mL/L. The addition of Aloe vera extract as many as 20 mL/L, 30 mL/L, 40 mL/L are able to reduce the total Coliform bacteria content in the river water into 24000 MPN/100 mL, 2400 MPN/100 mL, and 2400 MPN/100mL. It shows that Aloe vera extract is able to be used as natural disinfectant with optimum concentration 30 mL/L and 40 mL/L.